Біоконверсія промислових відходів у поверхнево-активні речовини Nocardia vaccinii ІМВ В-7405 - Берегова (Покора), Христина Андріївна (My University, 2017)
Дисертаційна робота присвячена розробці технологій поверхнево-активних речовин (ПАР) Nocardia vaccinii ІМВ В-7405 з використанням суміші промислових відходів, а також дослідженню практичного використання ПАР для контролю чисельності фітопатогенних бактерій. Розроблена технологія дає змогу отримати 13 г/дм3 ПАР за умов культивування N.vaccinii ІМВ В-7405 на технічному гліцерині (8 %) і мелясі (1 %), підвищення у два рази (до 1 г/дм3) вмісту нітрату натрію у середовищі культивування та використання 10 % інокуляту, вирощеного на суміші технічного гліцерину (0,25 %) і меляси (0,25 %). The dissertation thesis is devoted to а development of technology of surface-active substances (surfactants) synthesized by Nocardia vaccinii IMV B-7405 using a mixture of industrial waste, such as crude glycerol and molasses, and to investigation of practical use of surfactants. Production of surfactants is highly promising direction in the industry, since such connections have several advantages over synthetic analogs. Surfactants are widely used in various industries (environmental technologies, food processing, agriculture, medicine). The oil-oxidizing bacteria were isolated from the oil-polluted samples of soil and identified as Nocardia vacinii K-8 (IMV B-7405). The ability of these strain to synthesize the metabolites with surface-active and emulsifying properties was determined during the cultivation in medium with hydrophobic (n-hexadecane, liquid paraffin) and hydrophilic (glucose, ethanol) substrates was eatablished in previous studies. It was also determined that the chemical composition of surfactants synthesized by N. vacсinii K-8 on pure glycerol was a complex of neutral, glyco- and aminolipids. Glycolipids represented by trehalosediacelates and trehalosemycolates. Was showed that biosurfactant preparations of strain IMV В-7405 were effective against phytopathogenic bacteria. The possibility of replacing of pure glycerol for the surfactant biosynthesis by N.vaccinii IMV B-7405 with industry food waste (oil and fat industry, sugar, dairy industry, fried sunflower oil) was established.
Keywords: кафедра біотехнології і мікробіології; Nocardia vaccinii IMB В-7405; поверхнево-активні речовини; біоконверсія; технічний гліцерин; суміш субстратів; bioconversion; surfactants; waste of biodiesel production; mixture of substrates